2004
DOI: 10.1111/j.1399-5618.2004.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication use patterns and 2‐year outcome in first‐admission bipolar disorder with psychotic features

Abstract: The findings confirm clinical trial data that for some outcome measures use of antimanics is associated with good outcome in bipolar populations while failure to use these medications regularly was common among subjects with the worst outcomes. In addition, our findings that higher educational attainment and having health insurance predicted regular antimanic use and (for the latter) better outcome underscore the effect of socioeconomic influences while achieving a complete remission seems unrelated to medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
(38 reference statements)
2
25
0
Order By: Relevance
“…Another study, however, found that treatment outcomes were independent of baseline disease severity and psychiatric comorbidities (McIntyre et al 2007). Similar to the results of the present study, another group concluded that Caucasian ethnicity, but not medication use, was associated with remission (Craig et al 2004).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another study, however, found that treatment outcomes were independent of baseline disease severity and psychiatric comorbidities (McIntyre et al 2007). Similar to the results of the present study, another group concluded that Caucasian ethnicity, but not medication use, was associated with remission (Craig et al 2004).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies identifi ed disease severity and duration, number of prior hospitalizations, psychiatric comorbidities and age at disease onset as predictors of response (Zarate et al 2000;Welge et al 2004;Tohen et al 2007). Disease severity and psychiatric comorbidities were also associated with remission, as were number of previous depressive episodes and patient age (Craig et al 2004;Chengappa et al 2005;Kora et al 2008;Tohen et al 2007), whilst female gender predicted recovery (Tohen et al 2003). Another study, however, found that treatment outcomes were independent of baseline disease severity and psychiatric comorbidities (McIntyre et al 2007).…”
Section: Discussionmentioning
confidence: 91%
“…An epidemiologic study from the United States on first admission of bipolar patients with psychotic features suggested that more patients received antipsychotics (80.0 %) than lithium or antiepileptics (52.3 %) at discharge. After 2 years, 44.6 % reported using no medications, while 19.4 and 38.8 % were taking antipsychotics and antimanics, respectively [131].…”
Section: Pharmacoepidemiologymentioning
confidence: 99%
“…Recent evidence has demonstrated that 44.4% of children with bipolar I disorder will continue to experience manic episodes in adulthood (Geller et al 2008), suggesting continuity between childhood and adult bipolar I disorder. Therefore, initiating treatment in the pediatric age group may lead not only to symptomatic improvement in childhood and adolescence, but also to more positive outcomes in adulthood (Craig et al 2004;DelBello et al 2008).…”
Section: Introductionmentioning
confidence: 99%